NEK1 variants confer susceptibility to amyotrophic lateral sclerosis - Kenna, Kevin P.; Weishaupt, Jochen H.; Brown, Robert H.; Al-Chalabi, Ammar; Silani, Vincenzo; Shaw, Christopher E.; Berg, Leonard H. van den; Veldink, Jan H.; Landers, John E. (Nature genetics, 2016)
Jan Veldink and colleagues show that loss-of-function variants in NEK1 are associated with susceptibility to amyotrophic lateral sclerosis (ALS). In addition to finding an excess of rare loss-of-function NEK1 variants in ALS cases, they report a significant association between a specific NEK1 missense variant (p.Arg261His) and disease risk.